Legal mechanisms to enforce the polluter pays principle in the European Union - Rubene, Betija (Riga Graduate School of Law, 2023)
Over the past decades, humans have left a significantly destructive effect on the environment, leading to cause climate change, biodiversity loss, great levels of pollution and similar. One of the core principles that the European Union basis its environmental policy on, is the polluter pays principle, whose main idea is to set an obligation on the polluter to pay and remedy the pollution caused by their activities. This Bachelor Thesis aims to investigate the concept of the polluter pays principle, the relevance of it nowadays in EU law, and what are the main legal mechanisms of applying the polluter pays principle, within the framework of the European Union acquis, to ensure prevention and remediation of environmental damage, focusing on the Environmental Liability Directive, thus to ensure that the polluter is held liable for the pollution.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::Environmental law; Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Polluter Pays Principle; Environmental Liability